Design and development of solar powered aeration system - Wu, Daniel; Mohamed, Mohd Rusllim (2018)
With the drastic increment in the demand of aquaculture products i.e. fishes and crustaceans, the need to ensure good quality of products has been a major concern. Although literatures proven that there are three main factors affecting the quality, yet the mitigation aspect has yet to be explored. The current aeration system powered by grid electricity has also appeared to be costly based on ground survey. Therefore, in this project, a prototype of solar powered aeration system has been developed and 13 experiments on water quality have been carried out using the monitoring system prototype. From the experiments, it is found that temperature increment in the afternoon causes decrement in dissolved oxygen level while at night and during raining, oxygen content increases due to temperature drop and water movement caused by raindrops. Despite of these, the water condition is still not ideal for aquaculture farming due to high oxygen intake for fishes’ respiration. Therefore, when underwater aeration system is installed, it is found that the content of dissolved oxygen is sufficient to maintain ideal water condition as it compensate to the losses of dissolved oxygen caused by the factors studied. The solar stand-alone system is also able to provide sufficient electricity for the aeration system. Thus, with the help of monitoring system and solar powered aeration system, the quality of aquaculture product is able to be improved. This project increases the understanding of important factors in aquaculture farming to produce higher quality products in faster duration and the renewable energy potential in the country as source of electricity in aquaculture industry.